The broad-spectrum antiviral recommendations for drug discovery against COVID-19. (2nd July 2020) - Hazafa, Abu; ur-Rahman, Khalil; Haq, Ikram-ul-; Jahan, Nazish; Mumtaz, Muhammad; Farman, Muhammad; Naeem, Huma; Abbas, Faheem; Naeem, Muhammad; Sadiqa, Sania; Bano, Saira
Abstract: Despite to outbreaks of highly pathogenic beta and alpha coronaviruses including severe acute respiratory syndrome coronavirus (SARS-CoV), Middle East respiratory syndrome coronavirus (MERS-CoV), and human coronavirus, the newly emerged 2019 coronavirus (COVID-19) is considered as a lethal zoonotic virus due to its deadly respiratory syndrome and high mortality rate among the human. Globally, more than 3, 517, 345 cases have been confirmed with 243, 401 deaths due to Acute Respiratory Distress Syndrome (ARDS) caused by COVID-19. The antiviral drug discovery activity is required to control the persistence of COVID-19 circulation and the potential of the future emergence of coronavirus. However, the present review aims to highlight the important antiviral approaches, including interferons, ribavirin, mycophenolic acids, ritonavir, lopinavir, inhibitors, and monoclonal antibodies (mAbs) to provoke the nonstructural proteins and deactivate the structural and essential host elements of the virus to control and treat the infection of COVID-19 by inhibiting the viral entry, viral RNA replication and suppressing the viral protein expression. Moreover, the present review investigates the epidemiology, diagnosis, structure, and replication of COVID-19 for better understanding. It is recommended that these proteases, inhibitors, and antibodies could be a good therapeutic option in drug discovery to control the newly emerged coronavirus. Highlights: COVID-19 has more than 79.5% identical sequence to SARS-CoV and a 96% identical sequence of the whole genome of bat coronaviruses. Acute respiratory distress syndrome (ARDS), renal failure, and septic shock are the possible clinical symptoms associated with COVID-19. Different antivirals, including interferons, ribavirin, lopinavir, and monoclonal antibodies (mAbs) could be the potent therapeutic agents against COVID-19. The initial clinical trials on hydroquinone in combination with azithromycin showed an admirable result in the reduction of COVID-19. The overexpression of inflammation response, cytokine dysregulation, and induction of apoptosis could be an well-organized factors to reduce the pathogenicity of COVID-19.